An evaluation on the effects of safe person handling program implementation at long term care facilities for persons with complex intellectual, developmental, and medical conditions. Issue 4 (14th February 2023) - Ryan, Daniel; Anderson, Conor; Connolly, Ann Marie; Veety, Lindsey; Villavicencio, Tania; Parks, Lindsey
Abstract: Background: This retrospective chart review sought to determine whether the introduction of a safe person handling and mobility (SPHM) program resulted in changes to the frequency, severity, cost, or profile of staff injuries incurred during person handling (PH) tasks at long‐term care settings for persons with complex conditions. Methods: This study analyzed the SPHM program implementation at an organization providing long‐term residential, day habilitation, and special education services for persons with complex conditions. Data covered two 4‐year periods before and after implementation. Analyses compared the frequency, severity, and cost of staff PH injuries, as well as of the affected body area, staff role, level of treatment, and the incurred costs of Workers' Compensation (WC) claims. Results: There were substantive decreases in the total number of staff PH injuries and WC claims. Staff PH injuries affecting the trunk, the area most associated with PH injuries, decreased the most, followed by the upper extremities. Reductions were concentrated among direct care employees and their supervisors, job titles where PH exposures are most commonly seen. The proportion of staff injuries requiring medical treatment decreased significantly, as did injury severity. The number of lost workdays decreased by 94.6%. Incurred WC costs decreased by 91.1%. The proportion of WC claims associated with lost time decreased significantly. Conclusions: Substantive reductions in the frequency, severity, and incurred WC cost of staff PH injuries followed implementation of the SPHM program. Likewise, proportional changes were identified among the programs where cases occurred, the need for medical treatment, and WC cost type.